Human-Induced Pluripotent Stem Cells Manufactured Using a Current Good Manufacturing Practice-Compliant Process Differentiate Into Clinically Relevant Cells From Three Germ Layers - Shafa, Mehdi; Yang, Fan; Fellner, Thomas; Rao, Mahendra S.; Baghbaderani, Behnam Ahmadian (Frontiers in Medicine, 2018)
The discovery of reprogramming and generation of human induced pluripotent stem cells (iPSCs) has revolutionized the field of regenerative medicine and opened new opportunities in cell replacement therapies. While generation of iPSCs represents a significant breakthrough, the clinical relevance of iPSCs for cell based therapies requires generation of high quality specialized cells through robust and reproducible directed differentiation protocols. We have recently reported manufacturing of human iPSC master cell banks (MCB) under current good manufacturing practices (cGMP). Here, we describe the clinical potential of human iPSCs generated using this cGMP compliant process by differentiating them into the cells from all three embryonic germ-layers including ectoderm, endoderm, and mesoderm. Most importantly, we have shown that our iPSC manufacturing process and cell culture system is not biased towards a specific lineage. Following controlled induction into a specific differentiation lineage, specialized cells with morphological and cellular characteristics of neural stem cells, definitive endoderm, and cardiomyocytes were developed. We believe that these cGMP compliant iPSCs have the potential to make various clinically relevant products suitable for cell therapy applications.